2014
DOI: 10.1093/hmg/ddu357
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the human CBP4 ortholog UQCC3 impairs complex III assembly, activity and cytochrome b stability

Abstract: Complex III (cytochrome bc1) is a protein complex of the mitochondrial inner membrane that transfers electrons from ubiquinol to cytochrome c. Its assembly requires the coordinated expression of mitochondrial-encoded cytochrome b and nuclear-encoded subunits and assembly factors. Complex III deficiency is a severe multisystem disorder caused by mutations in subunit genes or assembly factors. Sequence-profile-based orthology predicts C11orf83, hereafter named UQCC3, to be the ortholog of the fungal complex III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 46 publications
5
55
0
Order By: Relevance
“…During the writing of the manuscript, Wanschers and colleagues proposed that C11orf83, which they renamed UQCC3, would be the human ortholog of Cbp4p. They identified a missense mutation in C11orf83 (Val20Glu) that resulted in the destabilization of the protein in a patient and caused a bc 1 complex deficiency (91). In addition to these findings, we have demonstrated that C11orf83 interacts with the bc 1 complex.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…During the writing of the manuscript, Wanschers and colleagues proposed that C11orf83, which they renamed UQCC3, would be the human ortholog of Cbp4p. They identified a missense mutation in C11orf83 (Val20Glu) that resulted in the destabilization of the protein in a patient and caused a bc 1 complex deficiency (91). In addition to these findings, we have demonstrated that C11orf83 interacts with the bc 1 complex.…”
Section: Discussionsupporting
confidence: 59%
“…We also demonstrated that C11orf83 is involved in the SC stabilization and binds to CL, two important features which had never been studied in yeast. Importantly, Wanschers and colleagues reported that cbp4⌬ mutant yeast strains could not be complemented by C11orf83 (91). This result could be due to a low level of sequence similarity between Cbp4p and C11orf83.…”
Section: Discussionmentioning
confidence: 99%
“…C11orf83 is currently known as an assembly factor of Complex III of the electron transport chain and is required for proper mitochondrial morphology and function. C11orf83-deficient cells displayed complex III assembly deficiency and abnormal mitochondria with an impaired oxidative phosphorylation3031. In the present study, we found that C11orf83 also is sensitive to viral infection, which was rapidly upregulated when cells were infected by VSV.…”
Section: Discussionsupporting
confidence: 56%
“…Patient cells with a homozygous c.59T > A missense mutation in C11orf83 have reduced complex III activity. The patient displays lactic acidosis, hypoglycemia, hypotonia, delayed development and severely delayed psychomotor development31. In the present study, we reported the identification of C11orf83 as a novel antiviral protein.…”
mentioning
confidence: 53%
“…Early identification of CoQ10 deficiency may be clinically meaningful as some patients with LS and CoQ10 deficiency respond to supplementation . Nuclear mutations for complex III (CIII) deficiency include BCS1L , TTC19 , CYC1 , UQCC2, 3 , LYRM7 and UQCRQ . Mutations in TTC19 are usually nonsense whereas in BCS1L they are missense although either can lead to a range of neurological symptoms.…”
Section: Genetic Basis Of Lsmentioning
confidence: 99%